2019
DOI: 10.3390/su11051435
|View full text |Cite
|
Sign up to set email alerts
|

Slow Steaming as Part of SECA Compliance Strategies among RoRo and RoPax Shipping Companies

Abstract: Many geographically peripheral member states of the EU are critically dependent on short sea Roll-on/Roll-off (RoRo) and mixed freight–passenger (RoPax) shipping services for intra-European trade. The implementation of the Sulfur Emission Control Area (SECA) regulation was expected to raise the operating cost for RoRo and RoPax shipping, and slow steaming was proposed as an immediate solution to save the increased cost. Previous research has investigated the issue of slow steaming and SECA using a quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…However, the feared negative economic consequences-such as modal shift to road, clients lost, and even relocation of cargo-owner industries-that were heatedly debated by the shipping sector before the regulation did not materialize. Companies operating on regular liner traffic in the Baltic Sea did not make any major route changes or schedule adjustments either, but many of them transferred the additional cost caused by SECA to their clients in the form of a bunker fee [66]. Raza, Woxenius and Finnsgård [66] show that contrary to prior expectations, slow steaming did not increase either among Ro-Ro and Ro-Pax shipping companies operating in the SECA.…”
Section: Seca-a Wake-up Call For the Baltic Sea Shipping Actorsmentioning
confidence: 87%
See 1 more Smart Citation
“…However, the feared negative economic consequences-such as modal shift to road, clients lost, and even relocation of cargo-owner industries-that were heatedly debated by the shipping sector before the regulation did not materialize. Companies operating on regular liner traffic in the Baltic Sea did not make any major route changes or schedule adjustments either, but many of them transferred the additional cost caused by SECA to their clients in the form of a bunker fee [66]. Raza, Woxenius and Finnsgård [66] show that contrary to prior expectations, slow steaming did not increase either among Ro-Ro and Ro-Pax shipping companies operating in the SECA.…”
Section: Seca-a Wake-up Call For the Baltic Sea Shipping Actorsmentioning
confidence: 87%
“…Companies operating on regular liner traffic in the Baltic Sea did not make any major route changes or schedule adjustments either, but many of them transferred the additional cost caused by SECA to their clients in the form of a bunker fee [66]. Raza, Woxenius and Finnsgård [66] show that contrary to prior expectations, slow steaming did not increase either among Ro-Ro and Ro-Pax shipping companies operating in the SECA. Their results show that in the Ro-Ro segment slow steaming is done on a small scale primarily to save fuel costs.…”
Section: Seca-a Wake-up Call For the Baltic Sea Shipping Actorsmentioning
confidence: 87%
“…The importance of the SSS, and in particular of Ro-Ro transport services, in the development of efficient and sustainable transport networks, is evident from the attention given to this sector both by the European Community [1,2] and by academic researchers. In the sector literature, several studies have been carried out in order to analyze the potential of maritime transport with reference to the efficiency of the Ro-Ro terminals [3][4][5] but also to the environmental sustainability of this kind of transport [6,7].…”
Section: Short Sea Shipping In the Mediterranean Sea Potentialities mentioning
confidence: 99%
“…Number sixth research area covers potential demand, opportunity, competitive advantage and sustainable transport development ( [38], [69], [101], [50], [90], [124], [32], [75], [110], [94], [74], [111], [70], [71], [58], [59], [109], [128], [119], and [126], [99], Eventually, only few studies can be traced that focus on the influence of meteorological or weather conditions on SSS operations ( [43], and [29],).…”
Section: Research Area In Sssmentioning
confidence: 99%
“…Similarly, Hamilton [44] employed the same approach to investigate the SSS network and finance model and suggested that proper consultation with stakeholders and design of the implementation can mitigate constraints. [101] also employed the Qualitative Methodology when they investigated on deliberate steaming as part of SECA acquiescence strategies among Ro-Pax and Ro-Ro shipping businesses and accomplish that bunker rates, rough competition and greatest importantly dissimilar service value requirements have expressively limited the latent application of deliberate steaming.…”
Section: Algorithmmentioning
confidence: 99%